2011
DOI: 10.1088/1751-8113/44/39/395201
|View full text |Cite
|
Sign up to set email alerts
|

Discrete integrable systems and hodograph transformations arising from motions of discrete plane curves

Abstract: We consider integrable discretizations of some soliton equations associated with the motions of plane curves: the Wadati-Konno-Ichikawa elastic beam equation, the complex Dym equation, and the short pulse equation. They are related to the modified KdV or the sine-Gordon equations by the hodograph transformations. Based on the observation that the hodograph transformations are regarded as the Euler-Lagrange transformations of the curve motions, we construct the discrete analogues of the hodograph transformation… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
38
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 43 publications
(40 citation statements)
references
References 79 publications
0
38
0
2
Order By: Relevance
“…We comment here that λ 1 is the reciprocal of the wave number p 1 in [31]. As discussed in [31], if λ Furthermore, by using the N -fold DT, we could drive the N -soliton solution through the formula (28):…”
Section: A Single Soliton Solution and N -Soliton Solutionmentioning
confidence: 99%
“…We comment here that λ 1 is the reciprocal of the wave number p 1 in [31]. As discussed in [31], if λ Furthermore, by using the N -fold DT, we could drive the N -soliton solution through the formula (28):…”
Section: A Single Soliton Solution and N -Soliton Solutionmentioning
confidence: 99%
“…In [59], we have shown that both the sine-Gordon equation and the SP equation can be derived from the motion of plane curves. The reciprocal link between them can be interpreted as Euler-Lagrangian transformation for the motion of plane curves.…”
Section: The Link Of the CD And The Sp Equations To The Motion Of Spamentioning
confidence: 99%
“…Finally, although integrable discretizations of the real and complex CD equations, as well as the real and CSP equations were recently constructed by several authors [33,59,[62][63][64], how to understand and reconstruct them within the framework of geometry remains a topic to be explored in the future.…”
Section: Comments and Further Topicsmentioning
confidence: 99%
“…In the last, the integrable discretizations for the CSP and the coupled CSP equations remain a topic to be explored in the future. Following a series work done by the authors regarding integrable discretizations of the real SP equation and its multicomponent generalizations [7,[53][54][55][56], we will construct the integrable discretizations of the focusing and defocusing CSP equation algebraically and clarify their geometric meaning within a general framework set in [57,58].…”
Section: Discussionmentioning
confidence: 99%